The Role of Work Environment, and Career Development - Kamaru, Sri Mulyaningsih (Yayasan Pendidikan Belajar Berdikari, 2023)
The goal of this study was to examine the impact of workload, work environment, and career development on PT Makassar Indah Graha Sarana employee performance. This study's population was only PT Makassar Indah Graha Sarana employees, and the sample size was 96 employees. This research approach collects primary data through the use of a questionnaire. Data processing findings include a description of the respondent's identity, variable descriptions, validity test results, reliability test results, F test results, coefficient of determination (R2) test results, and hypothesis testing results. According to the study's findings, workload has a positive and substantial impact on employee performance, work environment has a favourable and major impact on employee performance, and career development has a positive and significant impact on employee performance.